Transcriptomic and biochemical analysis from the venom gland of the neotropical ant Odontomachus chelifer - Guimarães, Denise Oliveira; Ferro, Milene [UNESP]; Santos, Thamires Silva; Costa, Tassia Rafaela; Yoneyama, Kelly Aparecida Geraldo; Rodrigues, Veridiana de Melo; Henrique-Silva, Flávio; Rodrigues, Renata Santos (Elsevier, 2023)
The genus Odontomachus is widely distributed in neotropical areas throughout Central and South America. It is a stinging ant that subdues its prey (insects) by injecting them a cocktail of toxic molecules (venom). Ant venoms are generally composed of formic acid, alkaloids, hydrocarbons, amines, peptides, and proteins. Odontomachus chelifer is an ant that inhabits neotropical regions from Mexico to Argentina. Unlike the venom of other animals such as scorpions, spiders and snakes, this ant venom has seldom been analyzed comprehensively, and their compositions are not yet completely known. In the present study, we performed a partial investigation of enzymatic and functional activities of O. chelifer ant venom, and we provide a global insight on the transcripts expressed in the venom gland to better understand their properties. The crude venom showed phospholipase A2 and antiparasitic activities. RNA sequencing (Illumina platform) of the venom gland of O. chelifer generated 61, 422, 898 reads and de novo assembly Trinity generated 50,220 contigs. BUSCO analysis against Arthropoda_db10 showed that 92.89% of the BUSCO groups have complete gene representation (single-copy or duplicated), while 4.05% are only partially recovered, and 3.06% are missing. The 30 most expressed genes in O. chelifer venom gland transcriptome included important transcripts involved in venom function such as U-poneritoxin (01)-Om1a-like (pilosulin), chitinase 2, venom allergen 3, chymotrypsin 1 and 2 and glutathione S-transferase. Analysis of the molecular function revealed that the largest number of transcripts were related to catalytic activity, including phospholipases. These data emphasize the potential of O. chelifer venom for prospection of molecules with biotechnological application.
Keywords: Ant venom; Anti-parasite; Odontomachus chelifer; Phospholipases; Transcriptomic analysis